Normative reference values for handgrip strength in colombian schoolchildren: The fuprecol study (2017)
Ramírez-Vé lez, R, Morales, O, Peñ a-Ibagon, JC, Palacios- Ló pez, A, Prieto-Benavides, DH, Vivas, A, Correa-Bautista, JE, Lobelo, F, Alonso-Martínez, AM, and Izquierdo, M. Normative reference values for handgrip strength in Colombian schoolchildren: The FUPRECOL study. J Strength Cond Res 31(1): 217-226, 2017-The primary aim of this study was to generate normative handgrip (HG) strength data for 10 to 17.9 year olds. The secondary aim was to determine the relative proportion of Colombian children and adolescents that fall into established Health Benefit Zones (HBZ). This cross-sectional study enrolled 7,268 schoolchildren (boys n = 3,129 and girls n = 4,139, age 12.7 [2.4] years). Handgrip was measured using a hand dynamometer with an adjustable grip. Five HBZs (Needs Improvement, Fair, Good, Very Good, and Excellent) have been established that correspond to combined HG. Centile smoothed curves, percentile, and tables for the third, 10th, 25th, 50th, 75th, 90th, and 97th percentile were calculated using Cole's LMS method. Handgrip peaked in the sample at 22.2 (8.9) kg in boys and 18.5 (5.5) kg in girls. The increase in HG was greater for boys than for girls, but the peak HG was lower in girls than in boys. The HBZ data indicated that a higher overall percentage of boys than girls at each age group fell into the 'Needs Improvement' zone, with differences particularly pronounced during adolescence. Our results provide, for the first time, sex-And age-specific HG reference standards for Colombian schoolchildren aged 9-17.9 years. © 2016 National Strength and Conditioning Association.